Influence of zinc oxide on the physical, structural and optical band gap of zinc silicate glass system from waste rice husk ash - Lee, Chee Sun; Matori, Khamirul Amin; Ab Aziz, Sidek; Mohamed Kamari, Halimah; Ismail, Ismayadi; Mohd Zaid, Mohd Hafiz (Elsevier, 2017)
Zinc silicate (ZnO-SiO2) glass was fabricated using melt-quench technique with compositions according to the empirical formula [(ZnO)x(WRHA)1-x] which x = 0.50, 0.55, 0.57 wt.%. These glass series acquire zinc oxide (ZnO) and white rice husk ash (WRHA) as silica source with two different melting temperatures of 1450 °C and 1500 °C. Temperature of 1450 °C and 1500 °C were chosen in this study because the lowest melting point of ZnO-SiO2 were at 1475 °C and by choosing a temperature within the range of 1475 °C a conclusive study on the best melting point using WRHA substituents can be done. Physical, structural and optical characteristics of fabricated glass samples were analyzed using Energy Dispersive X-ray Fluorescence (EDXRF), X-ray diffraction (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and UV–vis (UV–vis). Optical band gap of the system was obtained by approaching the optical absorption techniques from the Mott-Davis methods. Results indicate that ZnO-SiO2 glass samples emerge in favors of direct and indirect forbidden transition and increase in ZnO causes a higher absorption thus resulting in lower band gap. Last but not least, in this study based on the increase of ZnO content, the glass samples which contains a higher amount of ZnO has a higher band gap as Zn2+ ions reacts as good network modifier in the glass structure and formed a better arrangement and structure compared to system which has less network modifier.